Biocontrol: the response of native oystercatchers to a non‐native clam invasion. (5th July 2018) - Ferreira‐Rodríguez, Noé; Pardo, Isabel
Abstract : Global change, including invasive species introduction, has already had observable effects on migrant bird species, from northern breeding areas to wintering grounds. In this study we analyze the response of the Eurasian oystercatcher abundance to the density of an invasive clam species ( Corbicula fluminea ) and its potential role as biological control. As a case study, the oystercatcher population fluctuations over a 30‐yr time period, coupled with video‐recorded estimates of its feeding behavior on C. fluminea, and results from an exclosure experiment, were analyzed in the NW of the Iberian Peninsula. Results showed that oystercatchers exert a top‐down control over C. fluminea density. In addition, oystercatchers doubled its wintering numbers in a C. fluminea invaded estuary where they actively feed upon this invasive clam. Given that, the facilitative interaction between the invasive C. fluminea and the migratory Eurasian oystercatcher seems to respond to bottom‐up forces. Altogether, our results suggest that control measures applied to long term biological invasions must be carefully analyzed since non‐native species may be sustaining dependent native communities.